(untitled) (Práxis Educativa, 2018)
In this paper, the aim is to analyze how power relations currently (re)configure a supposed “ideal” Mathematics textbook, from the perspective of different characters who act in this production, whose actions impel the (re)configuration of this material. Based on Foucauldian theorizations on discourse analysis and knowledge-power relations, semi-structured interviews with authors of Mathematics textbooks, editors, collaborators, designers and teams of the National Textbook Program (known as PNLD) are taken as empirical material. The data show that, after a period of adjustments and improvements, post-evaluation of the PNLD, there is an adaptation of the Mathematics textbooks based on the current discourse, since more challenging proposals are penalized. As the Mathematics textbook becomes a commercially profitable product, potentially more salable works are built by official and marginal knowledge, forged in the multiplicity of power relations and in the reading of discourses that are in the order of the present time. Keywords: Mathematics textbook. Discourse analysis. Power relations.